Nacer - Diaro de Maternidad - Cabellero, Jorge (Spain, 2011)
Every day, in the maternity rooms of the public hospitals of Bogota, hundreds of women give birth. The mothers arrive on their own, exposed to machinery that neither knows affection nor comprehension. An observational camera gets very close to the women in pain giving a glimpse of their personal stories, but at the same time keeping a respectful distance. Questions arise while observing the scenery of one of the most intimate and meaningful acts on earth: what will be the future of those newborns? Birth is a montage of bitter and, at the same time, beautiful moments.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films